Jawabanmu

2013-12-10T20:58:40+07:00
Kalo soalnya :
(i) 2a+3b+4c = 1
(ii) a+3b+2c = -1
(iii) 4a+9c = -2

(i) 2a+3b+4c = 1
(ii) a+3b+2c = -1 -
         a+2c = 2 ... (iv)

(iii) 4a+9c = -2  [x1] 4a+9c = -2
(iv)  a +2c = 2   [x4] 4a+8c = 8 -
                                     c = -10

(iv) a+2c = 2
     a+2(-10) = 2
               a = 2+20
               a = 22

(ii) a+3b+2c = -1
   22+3b+2(-10) = -1
        3b + 2 = -1
              3b = -1-2
              3b = -3
                b = -1

itu jawabanku

salsa iya saya mengerti sekarang .. sepertinya memang salah persamaan satunya
iya